An Economic Analysis of Crime Costs Associated with Psychopathic Personality Disorder and Violence Risk - Gatner, Dylan T. (Criminal justice and behavior, 2023)
Given substantial national crime costs and that psychopathic personality disorder (PPD) is a robust predictor of recidivism, a research gap exists concerning the cost of crime attributable to adults with PPD. The current study employed a bottom-up cost of illness approach to estimate the association between PPD and crime costs among Canadian men incarcerated in the federal correctional system (n = 188). Participants were rated using the Psychopathy Checklist–Revised (PCL-R) and the Historical-Clinical-Risk Management–20 (HCR-20, version 2). Group mean crime costs were highest for participants who scored highly on the PCL-R and were rated high risk on the HCR-20, and higher scores on both measures were associated with prospective costs accrued from violent and nonviolent recidivism. The findings highlight the need to improve the treatment and management of high-risk individuals with prominent psychopathic features, as it has the potential for significant financial savings for criminal justice systems.